HPPMS deposition from composite targets: Effect of two orders of magnitude target power density changes on the composition of sputtered Cr-Al-C thin films. (November 2017) - Rueß, H.; to Baben, M.; Mráz, S.; Shang, L.; Polcik, P.; Kolozsvári, S.; Hans, M.; Primetzhofer, D.; Schneider, J.M.
Abstract: The effect of target power density, substrate bias potential and substrate temperature on the thin film composition was studied. A Cr-Al-C composite target was sputtered utilizing direct current (DCMS: 2.3 W/cm 2 ) and high power pulsed magnetron sputtering (HPPMS: 373 W/cm 2 ) generators. At floating potential, all Cr-Al-C thin films showed similar compositions, independently of the applied target power density. However, as substrate bias potential was increased to −400 V, aluminum deficiencies by a factor of up to 1.6 for DCMS and 4.1 for HPPMS were obtained. Based on the measured ion currents at the substrate, preferential re-sputtering of Al is suggested to cause the dramatic Al depletion. As the substrate temperature was increased to 560 °C, the Al concentration was reduced by a factor of up to 1.9 compared to the room temperature deposition. This additional reduction may be rationalized by thermally induced desorption being active in addition to re-sputtering. Highlights: Cr-Al-C films were deposited from a Cr-Al-C composite target by DCMS and HPPMS. Compositional deviations between composite target and thin films are observed. Increasing target power density and substrate bias potential enhance Al deficiency. Increasing substrate temperature enhances Al deficiency. Al deficiency is attributed to preferential re-sputtering and thermal desorption.